Analisis Kepuasan Masyarakat Terhadap Pelayanan Melalui E-Service Quality Di Kota Jambi - Navarin Karim; Hendriyaldi Hendriyaldi; Wahyu Rohayati (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
In the era of digitalization, every government agency is expected to be able to solve community problems quickly and be technology-based in facing the era of the industrial revolution 4.0. The government is not only required to provide conventional system services, but also to provide technology-based or electronic services. Then the creation of collaboration between employees and technology while serving the community. The research objective was to see the influence of public services on community satisfaction and the influence of e-service quality on community satisfaction in the Jambi City Government in the digitalization era. This research uses descriptive quantitative research. In this technical research, the data used a questionnaire method given to respondents who stated statements related to the object of research, namely public services, electronic service quality and community satisfaction. In this sampling research using purposive sampling technique. Purposive sampling is a sampling technique with considerations that meet the criteria.. The number of samples in this study were 60 people. Measurement using a Likert scale variable. The technique of testing the instrument for validity and reliability. Data analysis techniques used the help of the SPSS 21.0 application. The results showed that there was a significant positive effect of public services on community satisfaction, there was a significant positive effect on the e-services quality on community satisfaction, and there was a significant positive effect of public services and e-services quality on community satisfaction together with the Jambi City government.